Migrant tuberculosis patient needs and health system response along the Thailand-Myanmar border. - Tschirhart, N; Nosten, F; Foster, A (Oxford University Press, 2017)
This article aims to identify how the health system in Tak province, Thailand has responded to migrants' barriers to tuberculosis (TB) treatment. Our qualitatively driven multi-methods project utilized focus group discussions, key informant interviews, and a survey of community health volunteers to collect data in 2014 from multiple perspectives. Migrants identified legal status and transportation difficulties as the primary barriers to seeking TB treatment. Lack of financial resources and difficulties locating appropriate and affordable health services in other Thai provinces or across the border in Myanmar further contributed to migrants' challenges. TB care providers responded to barriers to treatment by bringing care out into the community, enhancing patient mobility, providing supportive services, and reaching out to potential patients. Interventions to improve migrant access and adherence to TB treatment necessarily extend outside of the health system and require significant resources to expand equitable access to treatment. Although this research is specific to the Thailand-Myanmar border, we anticipate that the findings will contribute to broader conversations around the inputs that are necessary to address disparities and inequities. Our study suggests that migrants need to be provided with resources that help stabilize their financial situation and overcome difficulties associated with their legal status in order to access and continue TB treatment.